Peran Kinerja Keuangan dalam memediasi Pemasaran digital Terhadap Keberlangsungan Hidup Pelaku UKM Pada Mitra Binaan PT. Perkebunan Nusantara III - Harianto, Adi; Honkley, Tony; Razaq, Mhd Restu; Nasib; Junaidi (JURNAL EKUIVALENSI, 2024)
This study aims to examine the role of financial performance in mediating the influence of pemasaran digital on the survival of Small and Medium Enterprises (SMEs) in PT. Perkebunan Nusantara III's Fostered Partners. This study uses a quantitative method with a survey involving 75 SMEs who are fostered partners of PT. Perkebunan Nusantara III. Data analysis was carried out using multiple linear regression and mediation tests to determine the role of financial performance in the relationship between pemasaran digital and SME survival. The results of the study indicate that pemasaran digital significantly affects financial performance, which then has a positive impact on SME survival. Financial performance has been shown to act as a strong mediator in increasing the impact of pemasaran digital on SME survival. These findings provide strategic guidance for SMEs and PT. Perkebunan Nusantara III managers to optimize the use of pemasaran digital to strengthen long-term business sustainability.